2017
DOI: 10.1115/1.4036262
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Method for Analyzing the Biomechanics of Arterial Bruits

Abstract: A computational framework consisting of a one-way coupled hemodynamic-acoustic method and a wave-decomposition based postprocessing approach is developed to investigate the biomechanics of arterial bruits. This framework is then applied for studying the effect of the shear wave on the generation and propagation of bruits from a modeled stenosed artery. The blood flow in the artery is solved by an immersed boundary method (IBM) based incompressible flow solver. The sound generation and propagation in the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Zhu et al [11] already demonstrated through a classic vector decomposition that the shear waves had a significant impact on the spectra of the murmurs and acoustic energy distribution on the epidermal surface, and inclusion of this effect in our study should lead to more realistic modeling of murmur propagation.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Zhu et al [11] already demonstrated through a classic vector decomposition that the shear waves had a significant impact on the spectra of the murmurs and acoustic energy distribution on the epidermal surface, and inclusion of this effect in our study should lead to more realistic modeling of murmur propagation.…”
Section: Introductionmentioning
confidence: 74%
“…5) that the outlet of the aorta is not a source location. Also, based on the previous study [10,11], compression waves are convenient for predicting the source location due to its long wave length and better directionality.…”
Section: Murmur Propagation For 75% Stenosis Casementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, virtual Echocardiography (ECHO) and Phonocardiography (PCG) can *Corresponding author. C serve as a bridge between clinical data and computational hemodynamic results [27,28]. These virtual ECHO and PCG can be used for rapid validation of computational results by comparing to the actual cardiographic data, and furthermore, such comparisons will allow us to calibrate a given patientspecific, computational heart model.…”
Section: Introductionmentioning
confidence: 99%